BEHAVIOR OF STIFFENED DEEP CEMENT MIXING PILE IN LABORATORY - P. Jamsawang; D. T. Bergado; A. Bhandari; P. Voottipruex (International Association of Lowland Technology, 2009)
The low strength and stiffness of Deep Cement Mixing (DCM) pile causes unexpected failure that has been mitigated with the introduction of stiffened deep cement mixing (SDCM) pile. The SDCM is a new type of DCM pile reinforced by concrete core pile. In this paper, the interface behavior of SDCM pile and its strength have been studied by various laboratory tests. The cement content was varied from 10 to 20% by dry weight of clay and mixed at the water content corresponding to its liquid limit to obtain optimum strengths. The interface friction between the core concrete pile and the cement-admixed clay was studied by means of the direct shear tests and Ko interface shear tests. The 15% cement content yielded optimum interface shear strength. The CIU triaxial compression test of model SDCM pile revealed that the concrete core pile length should be more than 75% of the DCM pile length in order to have significant improvement.